Penertiban Pengemis dan Gelandangan oleh Satuan Polisi Pamong Praja Kota Padang - Hariandi Nofanki; Syamsir Syamsir (Policy, Law and Political Research Center, 2022)
This study aims to determine the performance of the Padang City Civil Service Police Unit in controlling homeless people and beggars in Padang City. To find out the strengths, opportunities, weaknesses, and threats faced by the Civil Service Police Unit in controlling beggars and homeless people in Padang City. And to find out what efforts or things need to be improved in the performance of the Satpol PP for controlling beggars and homeless people in the city of Padang. This type of research is qualitative research. The results of this study are: 1) Implementation of the performance of the Padang City Civil Service Police Unit in controlling homeless people and beggars has been carried out as much as possible and in accordance with Padang City Regulation No. 1 of 2012; 2) In controlling the sprawl, the Padang City Satpol PP has the power to patrol every day. Opportunity is that mobile members carry out patrols. The weakness is the lack of facilities and infrastructure. And the threat is that there are still sprawl from outside the city of Padang; 3) The efforts or things that need to be improved in the performance of the Satpol PP for controlling beggars and homeless people in Padang City, such as: Communication with the people of Padang City, facilities and infrastructure, cooperation with related OPD, and inadequate Padang City Satpol PP personnel.